Mengoptimalkan Kemampuan Berbahasa Anak Usia Dini Melalui Metode Bercerita - Nuzula Apriliyana, Firdausi (Universitas Nusantara PGRI Kediri, 2020)
Children's language skills in listening and speaking activities are not optimal, children's vocabulary is still limited, so that children in conveying ideas, answering questions, repeating stories and telling stories about their experiences have not been achieved as expected. The purpose of this research is to analyze the effect of storytelling methods on the development of language skills in early childhood. This type of research is an experimental study with a nonequivalent control group design. The research was carried out in KB 'Aisyiyah Mentari Tuban with 32 children as subjects. The number of subjects was divided into 2 groups, namely the control and experimental groups as a comparison of the development of language skills. Collecting research data using observation and documentation techniques. The validity test with the Pearson correlation and the reliability test with Cronbach Alpha were carried out first then analyzed the data with the t test. The results of this study were proven by using the storytelling method to optimize early childhood language skills. Calculation using the t-test for all indicators> t critical 1.7530, it can be concluded that H0 is rejected, H1 is accepted. This means that there is an effect of storytelling methods for all indicators on children's language skills. Suggestions for educators and PAUD institutions to implement storytelling methods as a method that can stimulate children's language skills. Keywords: Storytelling Method, Language Ability